Sentiment Analysis for YouTube Comments and Video Using AI - B. Venkatesh; GVS Ananthanath (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The YouTube Comments and Videos Sentiment Analysis project is a sophisticated system designed to automatically classify the sentiments of comments and video transcripts linked to YouTube videos. By leveraging Natural Language Processing and state-of-the-art deep learning models, it can identify whether the sentiments expressed are positive, negative, or neutral. This system makes use of tools like the YouTube Data API to pull in comments and the YouTube Transcript API to gather video transcripts. It employs advanced preprocessing techniques such as tokenization, lemmatization, and stop word removal to get the text ready for sentiment analysis. The project utilizes pre-trained models, including BERT for analyzing comment sentiments and LSTM and GRU for assessing video transcript sentiments, which helps ensure high accuracy in classification. Users can engage with the system through a web-based interface where they simply enter a YouTube video URL. The system then fetches the comments and transcripts, conducts sentiment analysis, and presents the findings in a user-friendly graphical format. It evaluates the models using metrics like accuracy, precision, recall, and F1-score, which helps confirm the system’s reliability.